Standing shock prevents propagation of sparks in supersonic explosive flows - Jens von der Linden (Nature Portfolio, 2021)
Images of electrical sparks in shock tube experiments with supersonic outflows show how standing shocks regulate electrical breakdown. The resulting radio frequency emission could diagnose flow structure in other explosive events such as volcanic eruptions.